Case Report: Huge Dumbbell-Shaped Primary Hydatid Cyst Across the Intervertebral Foramen - Tian, Yu; Jiang, Mei; Shi, Xin; Hao, Yujun; Jiang, Lei (Frontiers in Neurology, 2020)
Primary hydatid cyst of the spinal canal is extremely rare. We reported a 42-year-old Kazakh man with right lower back pain and weakness in both lower limbs for 2 months, who lived in the pastoral area. Clinical examination revealed that the patient had no cysts on other organs and no previous medical history except for a huge cyst inside and next to the vertebrae. MRI examination revealed a huge dumbbell-shaped primary cyst across the intervertebral foramen. Pathological examination after operation confirmed a fine-grained hydatid cyst disease. Therefore, in the pastoral area, doctors should be alert to the occurrence of hydatid cyst disease if patients complained about progressive back pain and lower limb weakness or other spinal cord compression symptoms. Once hydatid cysts in other organs or systems were detected, the occurrence of the disease could be highly suspected. Complete resection is an effective treatment for hydatid cyst disease.